AN AUDIT OF THE ACCURACY OF DRUG PRESCRIPTION INFORMATION ON TRANSFER LETTERS FROM THE PAEDIATRIC INTENSIVE CARE UNIT. Issue 8 (11th July 2014) - Kokoskova, A; Fletcher, P
Abstract : Aim: To audit the accuracy of prescribing following transfer from a Paediatric Intensive Care Unit using electronic prescribing. Methods: Historical data: Transfer from PICU letters sent to both external Trusts and wards within the same hospital were randomly selected pre and post the electronic prescribing system upgrade (July 2012) and compared with the final prescription screen of the inpatient electronic prescription record (EPR). Current data: For patients transferred to a ward of the same hospital between 17 December 2012 and 28th January 2013, the first handwritten drug chart after transfer from PICU was also reviewed for accuracy in comparison to the PICU EPR. Audit standard: 100% of patients transferred from PICU have correct transfer from PICU letters with regard to prescribed medicines. 100% of patients transferred from PICU to a ward within the hospital have correct transfer from PICU letters and correct first inpatient drug chart. Results: Data were collected for 16 patients pre-upgrade: 6 had correct transfer letters, 10 (63%) had errors. Among the 85 drugs prescribed, there were 12 errors involving 12 drugs (14% of drugs). After the July 2012 upgrade 14 patients were analysed, 10 had correct transfer letters, 4 (29%) had errors. Of the 80 drugs prescribed there were 8 errors (10% of drugs documented in the letters were wrong). Data were collected for 13 patients transferred to wards within the hospital; 9 (69%) had correct transfer letters and a correct first inpatient drug chart. Two patients had errors on their transfer letter and first drug chart, and two had errors on the transfer letter but the drug chart was correct (due to ward pharmacist intervention). There were 6 errors in total for these 4 patients. Errors included incorrect gentamicin and vancomycin doses and incorrect information about whether patients still required morphine, azithromycin and ceftriaxone. Following this audit a meeting was held with senior PICU consultants. The EPR software company have been contacted to improve the automated transfer letter system. Meanwhile the automated transfer letter has been modified to exclude drugs and junior doctors are requested to input this data manually. The signing consultant is reminded to check the prescription section carefully to prevent errors. Discussions are ongoing for nurses to be part of the checking process. Conclusion: Transfer letters are not being thoroughly checked before being sent with the patient on transfer from PICU. Some errors were due to a system failure where dose changes were not pulled across to the transfer letter. This did not resolve after the July 2012 upgrade. Errors appear to have reduced over the data collection period however this is anecdotally due to a raised awareness of the system failures and some junior doctors writing their own drug list rather than relying on the system to generate it. In order to meet expected standards of 100% correct information on transfer letters much closer attention must be paid to final accuracy checks.